An Analysis of Symbols Object In The Serarang Ritual In Melanau Community - Noor Norazila Inai; Mohamad Maulana Magiman; Norhuda Salleh (Human Resource Management Academic Research Society (HRMARS), 2022)
The Serarang ritual is an annual ritual that must be performed by the Melanau Likow community in preparation for the new year. Tama Kaul is the main leader in the implementation of this ritual with the use of symbols in the form of objects. Each object used contains a specific meaning, interpreted and agreed upon by its practicing community. The local wisdom possessed by this community of practitioners is inherited from one generation to another. Till this day, the practicing community still clings to the beliefs they inherited even although some of them have converted from their original religion. Therefore, this study aims to analyse the meaning of object symbols in the implementation of Serarang rituals. This study used an ethnographic approach through participatory observation, recording and photographic methods as well as a series of interviews with Tama Kaul and the ritual practitioners. The study location was located in Kampung Medong, Dalat Sarawak. Data analysis found that there were five object ritual symbols used to accompany the Serarang ritual namely kubo beliseng, beliseng, dian, the blood of rooster's feet and percak cloth. Among the meanings of symbols supported by these object symbols are the meanings of respect, purity, prayer and hope, peace between the two worlds and love. The results of this study also found that this ritual is still practiced by the Melanau Likow community until this day and becomes the identity of their existence in Sarawak.